Immunomodulation by Processed Animal Feed: The Role of Maillard Reaction Products and Advanced Glycation End-Products (AGEs) - Teodorowicz, Malgorzata; Hendriks, Wouter H.; Wichers, Harry J.; Savelkoul, Huub F. J. (Frontiers in Immunology, 2018)
The immune system is involved in host defense against infectious organisms and in assuring tolerance to sources of non-threatening antigens. Impaired immune function can be associated with increased susceptibility to infectious agents and increased severity of infections necessitating the therapeutic use of antibiotics. Malnutrition and specific nutrient deficiencies can impair immune function and increase susceptibility to infection. However, the impact of these immune system changes on the health of animals is less clear. Livestock performance and feed efficiency are closely interrelated with the qualitative and quantitative microbial load of the animal gut, the morphological structure of the intestinal wall and the activity of the immune system, which is modulated by dietary components. The majority of feeds that are consumed in livestock have been processed to some extent. Processing promotes a non-enzymatic reaction between proteins and sugars called the Maillard reaction (MR). Maillard reaction products (MRPs) and advanced MRPs (AGEs, advanced glycation end products) determine taste, smell and color of many food products therefore the MR is highly relevant for the feed industry. Maillard reaction products interact with the receptor for AGEs (RAGE) and immunomodulatory potential of feed proteins can be modified by the Maillard reaction. This reaction has become an important concern since MRPs/AGEs have been shown to contribute to increasing prevalence of diet-related chronic inflammatory states in the gut with negative health consequences and performance. This review highlights immunological mechanisms underlying initiation of the innate and adaptive immune responses by MRPs/AGEs, which are currently not completely understood. Bridging this knowledge gap will significantly improve nutritional quality of feed and increase the prevention of diet-mediated inflammation in animals.